ANALISIS PERUBAHAN KADAR NIKEL LATERIT DARI FRONT PENAMBANGAN KE STOCKPILE DI PT. WAHYU ANGGI SELARAS, KECAMATAN POMALAA, KABUPATEN KOLAKA, SULAWESI TENGGARA. - Imam Akhmad; Hendro Purnomo; Bayurohman Pangacella Putra (ReTII, 2022)
Wahyu Anggi Selaras is a contractor company at PT. Putra Mekongga Sejahtera, which is engaged in the mining of Laterite Nickel ore in Pomalaa sub-district, Kolaka district, Southeast Sulawesi. Nickel laterite is one of the mineral deposits resulting from the chemical weathering process of ultramafic rocks which results in residual and secondary enrichment of Ni, Fe, Mn, and Co elements. In mining activities for laterite nickel ore, there is often a delution of the elemental content of nickel ore when it is still on the mining front and after being moved to the stockpile, there may be significant changes in grades. The purpose of this study was to analyze the dellution percentage of grades that occur in laterite nickel minerals from the mining front after being moved to the stockpile and determine the factors that occur in these dellution grades. The research method used in this study is a statistical calculation method such as calculating the statistical average, the average difference test method using the t dependent test method and the Pearson correlation analysis method to find out how the relationship between the grades of each element contained in laterite nickel ore. From the results of the study, it was found that there was a dellution of nickel content from the mining front to the stockpile, where from the results of laboratory analysis it was found that the Ni content from the mining front was 2.11% while from the stockpile it was 1.93%. The Fe content from the front is 13.61% while the stockpile is 13.02%, the SiO2 content from the front is 30.63% while the stockpile is 32.33%, and the MgO content from the mining front is 16.85% while from the stockpile obtained MgO levels of 17.43%. From the results of the average difference test, it can be concluded that the changes that occur are significant changes and from the results of the correlation analysis it is found that only the values ​​of Ni and Fe in the stockpile have a relationship. Factors that change the levels are the lack of accuracy in sampling, manual sample preparation, human error factors and the pad or base in the pile of excavated materials still contains impurities. Keyword : Grades, Nickel, Front, Stockpile.